The association between sleep quality and attenuated psychotic symptoms. Issue 4 (16th July 2020) - Clarke, Stephen; Hanna, Donncha; Davidson, Sarah; Shannon, Ciarán; Mulholland, Ciaran
Abstract: Aim: To determine if poor sleep makes a unique contribution in predicting the likelihood of experiencing six or more attenuated psychotic symptoms and associated distress, after examining and controlling for sociodemographic factors, depression and drug/alcohol use. Method: An online survey was conducted using Amazon's online crowdsourcing service Mechanical Turk (MTurk). The sample was 1013 adults (18 to 36 years) from the general population in the United States. The survey consisted of the Prodromal Questionnaire 16 (PQ‐16), the Pittsburgh Sleep Quality Index, the Patient Health Questionnaire 9, the Drug Abuse Screening Test 10 and the Alcohol Use Disorders Identification Test. Regression analyses were performed with the PQ‐16 as the dependent variable, and sleep quality as the predictor variable, holding constant sociodemographic variables, depression, and alcohol/drug abuse. Results: 37% of the sample endorsed six or more PQ‐16 items, which may be suggestive of an at‐risk mental state, with sleep disturbance significantly increasing the likelihood (Odds ratio 2.09 < .001) of endorsing six or more PQ‐16 items. After controlling for sociodemographic variables, depression and drug/alcohol abuse, poor sleep quality made a unique contribution of 5.8% of the variance accounted for in level of distress experienced by attenuated psychotic symptoms. Conclusion: Effective treatment of sleep disturbance may reduce the likelihood ofexperiencing attenuated psychotic symptoms and associated distress.